Raw material consumption of the European Union - concept, calculation method, and results - Schoer, Karl; Giegrich, Jürgen (Environmental science & technology, 2012)
This article presents the concept, calculation method, and first results of the “Raw Material Consumption” (RMC) economy-wide material flow indicator for the European Union (EU). The RMC measures the final domestic consumption of products in terms of raw material equivalents (RME), i.e. raw materials used in the complete production chain of consumed products. We employed the hybrid input-output life cycle assessment method to calculate RMC. We first developed a highly disaggregated environmentally extended mixed unit input output table and then applied life cycle inventory data for imported products without appropriate representation of production within the domestic economy. Lastly, we treated capital formation as intermediate consumption. Our results show that services, often considered as a solution for dematerialization, account for a significant part of EU raw material consumption, which emphasizes the need to focus on the full production chains and dematerialization of services. Comparison of the EU’s RMC with its domestic extraction shows that the EU is nearly self-sufficient in biomass and nonmetallic minerals but extremely dependent on direct and indirect imports of fossil energy carriers and metal ores. This implies an export of environmental burden related to extraction and primary processing of these materials to the rest of the world. Our results demonstrate that internalizing capital formation has significant influence on the calculated RMC.